2016
DOI: 10.1007/s12311-015-0758-5
|View full text |Cite
|
Sign up to set email alerts
|

Body Sway Increases After Functional Inactivation of the Cerebellar Vermis by cTBS

Abstract: Balance stability correlates with cerebellar vermis volume. Furthermore, the cerebellum is involved in precise timing of motor processes by fine-tuning the sensorimotor integration. We tested the hypothesis that any cerebellar action in stance control and in timing of visuomotor integration for balance is impaired by continuous theta-burst stimulation (cTBS) of the vermis. Ten subjects stood quietly and underwent six sequences of 10-min acquisition of center of foot pressure (CoP) data after cTBS, sham stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 85 publications
2
25
1
Order By: Relevance
“…The anterior vermis also contains a complete somatosensory map of the body (Kandel, Schwartz, Jessell, Siegelbaum, & Hudspeth, ). Furthermore, it plays a key role in maintaining balance through somatosensory integration of visual and proprioceptive inputs and facilitates execution of body movements (Colnaghi, Honeine, Sozzi, & Schieppati, ) using sensory feedback to control muscle tone and movements (Kandel et al, ). At the same time, the vermis is considered part of the limbic cerebellum, crucial for motivation and emotion processing (O'Halloran, Kinsella, & Storey, ; Schmahmann, ; Schutter & van Honk, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior vermis also contains a complete somatosensory map of the body (Kandel, Schwartz, Jessell, Siegelbaum, & Hudspeth, ). Furthermore, it plays a key role in maintaining balance through somatosensory integration of visual and proprioceptive inputs and facilitates execution of body movements (Colnaghi, Honeine, Sozzi, & Schieppati, ) using sensory feedback to control muscle tone and movements (Kandel et al, ). At the same time, the vermis is considered part of the limbic cerebellum, crucial for motivation and emotion processing (O'Halloran, Kinsella, & Storey, ; Schmahmann, ; Schutter & van Honk, ).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior vermis also contains a complete somatosensory map of the body (Kandel, Schwartz, Jessell, Siegelbaum, & Hudspeth, 2012). Furthermore, it plays a key role in maintaining balance through somatosensory integration of visual and proprioceptive inputs and facilitates execution of body movements (Colnaghi, Honeine, Sozzi, & Schieppati, 2017) using sensory feedback to control muscle tone and movements (Kandel et al, 2012 2005). Depression and anxiety disorders have been linked to abnormalities in the anterior vermis structure and functionality (Schutter, 2013 Moreover, increased levels of state anxiety correlated positively with increased functional connectivity of the anterior vermis with the fusiform gyrus.…”
Section: Anterior Vermis 431 | Between-group Comparisonmentioning
confidence: 99%
“…Firstly, FS interneurons selectively amplify gamma frequencies through subthreshold resonance [ 33 ]. Secondly, gap junctions between inhibitory interneurons [ 27 ] have been shown to enhance synchrony [ 24 , 26 , 35 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al ( 2017 ) investigated the behavioral consequences of Ano2 absence and found that Ano2 knockout mice had significant deficits in their motor learning performance during classical eyeblink conditioning, a cerebellar dependent task where a conditioned stimulus (light/sound) predicts the arrival of an unconditioned stimulus (air puff). However, the idea that a cerebellar related dysfunction in behavior can solely be due to IO expression of Ano2 has recently been put to question (Neureither et al, 2017 ). In this study, Neureither et al ( 2017 ) proposed the previously mentioned depolarization-induced depression of inhibition in PCs to be the main cause for the motor deficits found in their Ano2 knockout model.…”
Section: Ca 2+ -Activated CL − mentioning
confidence: 99%
“…However, the idea that a cerebellar related dysfunction in behavior can solely be due to IO expression of Ano2 has recently been put to question (Neureither et al, 2017 ). In this study, Neureither et al ( 2017 ) proposed the previously mentioned depolarization-induced depression of inhibition in PCs to be the main cause for the motor deficits found in their Ano2 knockout model. In this respect, it is important to emphasize that even though the Ano2 protein is abundantly expressed in the IO, there is also evidence for its expression in other brain areas involved in motor function, including the thalamus (Table 2 ).…”
Section: Ca 2+ -Activated CL − mentioning
confidence: 99%